Afghanistan Development Update, April 2021 : Setting Course to Recovery - World Bank (World Bank, Washington, DC, 2021)
Afghanistan continues to face daunting challenges and uncertainties. The Coronavirus (COVID-19) crisis imposed a heavy burden on the economy, public finances, and private sector investment in 2020. Urban unemployment and hardship increased, while declining revenues limited the feasible extent of the government’s response. With many firms closed and jobs lost, recovery from the impacts of the crisis now depends on re-investment and a recovery in confidence. Restoration of confidence has been hampered, however, by challenging political and security conditions, and uncertainties regarding future international support. Peace talks between the government and the Taliban are making slow progress, while the frequency of Taliban attacks has increased. Economic recovery will depend on a continued strong partnership between the government and its international partners. To help restore private sector confidence and facilitate continued international support, the government needs to demonstrate substantial progress on revenue, anti-corruption, and private sector reforms.